A evasão escolar no ensino técnico profissionalizante : um estudo de caso no campus Cariacica do Instituto Federal do Espírito Santo - Meira, Cristiane Araújo (2015)
This paper deals with the school evasion characterized by student’s leaving school of his course of origin, at any stage, without completing it. It also tried to analyze and understand this phenomenon in the classes of the Technical Course in entering Railways Course between 2006 and 2014, in the high school concurrent mode, offered by Campus Cariacica at the Federal Institute of Espírito Santo. This study was justified by the relevance of the theme that is present in all forms of education and it worries many professionals in education due to the consequences it brings for the whole society. In spite of this, few researches turn to the area of professional technical education. The objective was to verify the amount of dropout students and the reasons that led to this decision and identify the characterizations that let the propellant context of abandonment happens in order to understand their occurrence and reflect on compelling alternative to solve the problem. The studies were based on bibliography, documentary and field research. These procedures for data collection consisted of documentary analysis of the transcripts of students and semistructured interviews with a sample of dropout students, which allowed the quantitative and qualitative analysis of information. The presentation of quantitative data statistically systematized alerted us to this high dropout rate in all classes offered, with percentages of evasion ranging from 23.44% to 62.85%.On the other hand, the qualitative analysis found the existence of internal and external factors to the institution as motivators of school evasion, influenced by a set of related situations both to the student and to the school. According to these results, it’s possible to point out the need for broadening and deepening the discussion on the subject in order to have a greater clarification and a visibility of the problem aiming to guide transformative actions to be implemented in each school reality identified from the awareness and commitment of all those involved